2020
DOI: 10.1111/1471-0307.12698
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties and organoleptic aspects of ice cream enriched with microencapsulated pistachio peel extract

Abstract: The purpose of this study was to produce a functional ice cream by the addition of microcapsules of pistachio peel extract (MPPE). Various properties of the resulting ice cream were investigated. By increasing the amount of MPPE the total phenolic content and antioxidant activity increased about 2.0‐ and 3.7‐fold, respectively, compared with the control sample. The rheological properties of the mixes were fitted by the Power Law model. All mixes showed non‐Newtonian pseudoplastic behaviour. By increasing the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 26 publications
5
20
0
Order By: Relevance
“…Rossa et al (2012) noted that whey protein thermally unfolds in the ice cream mixture and leads to the formation of protein polymers, which can behave like hard spheres, showing high flow resistance, thereby increasing the viscosity of the ice cream. Yazdi et al (2020) the ice creams elaborated in the present work were fitted by the Power law model. Therefore, the Power-law model described well the flow behavior of ice cream with the high correlation coefficient (Table 5), being (n = 1), confirming the Newtonian behavior (Figure 6).…”
Section: Ice Cream Analysismentioning
confidence: 99%
“…Rossa et al (2012) noted that whey protein thermally unfolds in the ice cream mixture and leads to the formation of protein polymers, which can behave like hard spheres, showing high flow resistance, thereby increasing the viscosity of the ice cream. Yazdi et al (2020) the ice creams elaborated in the present work were fitted by the Power law model. Therefore, the Power-law model described well the flow behavior of ice cream with the high correlation coefficient (Table 5), being (n = 1), confirming the Newtonian behavior (Figure 6).…”
Section: Ice Cream Analysismentioning
confidence: 99%
“…A hundred grams of solidified ice cream give our body approximately 190–214 calories (Bajwa et al., 2003; Khan et al., 2018). Ice cream is typically high in carbs but, low in dietary fibers and phenolic compounds (Ghandehari et al., 2020). Ice cream processing has drastically improved during the past 20 years, food manufacturers and research scientists have incorporated functional additives in ice cream for enhanced taste and nutritional content (Al, Ersoz, Ozaktaş, Turkanoglu, & Kucukcetin, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Ice cream is world-famous high-vital emulsified milk sweets made from air cells milk fat, colloidal protein, fortifiers (Ghandehari, Barzegar, Gavlighi, Sahari, & Mohammadian, 2020;Pintor, Escalona, & Totosaus, 2017), stabilizers, emulsifiers, sweeteners, and colors (Cavender & Kerr, 2020;Panwar, Shubhashini, & Kapoor, 2019). It is one of the most commonly offered and enjoyed by youngsters and other age people around the world (Ayar, Siçramaz, Ozturk, & Ozturk, 2018;Azari, Khomeiri, Ghafouri, & Aghajani, 2017;Caniyilmaz, Uçarkuş, & Karaman, 2016).…”
mentioning
confidence: 99%
“…In the WA test, ice cream was described mainly in the categories tasty, innovation, sweet taste, plant flavor, smooth and creamy, and the acceptance index was 74% (Mazon et al 2020) In a study was added addition of microcapsules of pistachio peel extract (MPPE) to produce a functional ice cream, The addition of MPPE to ice cream mixes improved the melting resistance, first dripping times and functional properties of ice cream such as antioxidant activity and total phenolic content. The results of the sensory analysis showed that the addition of MPPE had no significant effect on the overall acceptability of the product (Ghandehari Yazdi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%